Ascomycetes (Pezizomycotina, Ascomycota) de Brasil: nuevos registros y datos de distribución de las especies - Trierveiler-Pereira, Larissa (Lilloa, 2014)
Trierveiler-Pereira, Larissa. 2014. “Ascomycetes (Pezizomycotina, Ascomycota) from Brazil: New records and contributions to distributional data”. Lilloa 51 (1). Six species of ascomycetes are described and illustrated herein: Trichocoma paradoxa (Eurotiales), Moelleriella verruculosa (Hypocreales), Galiella spongiosa (Pezizales), Entonaema liquescens, Xylaria magnoliae var. microspora, and X. poitei (Xylariales). Xylaria poitei is reported for the first time from Brazil, and additional data on the distribution of the other species are presented.